Renovación Urbano Sectorial Av. Ferrocarril en Ibagué, Tolima - Sandoval Fernández, Jaime Andrés (Universidad Antonio Nariño, 2023)
Currently, all the cities of the world , vivienda, espacio público . face a problem of road mobility, due to the lack of architectural planning due to the growth of the population and the number of vehicles. For this reason, this work starts from the historical conformation of the roads of the municipality of Ibagué, in ord er to analyze the causes of road mobility problems, making use of the topographic plans of the main sectors, to propose collective changes that allow development economically. the municipality, such as the consolidation of linear parks or green spaces with trails throughout the city , developing new homes for households (families) in commune 10 of the city of Ibague